Relationship Between Emotional Intelligence, Self-Acceptance, and Positive Coping Styles Among Chinese Psychiatric Nurses in Shandong - Lu, Qinghua; Wang, Bin; Zhang, Rui; Wang, Juan; Sun, Feifei; Zou, Guiyuan (Frontiers in Psychology, 2022)
Background: Nurses are facing increasing pressure due to the progressing of society, broadening of nursing service connotation, and increasing of the masses' demand for medical treatment. Psychiatric nurses face suicides, violence, and lost along with other accidents involving patients with mental disorders under higher psychological pressure. A coping style, which is affected by individual emotions and cognition, is an essential psychological resource that allows individuals to regulate stress. The purpose of this study was to investigate the correlation between self-acceptance and the positive coping style of psychiatric nurses, and investigate the mediating role of emotional intelligence. Methods: A total of 813 psychiatric nurses from six natural regions in Shandong Province were investigated using the Self-Acceptance Questionnaire, Emotional Intelligence Scale (EIS), Simplified Coping Style Questionnaire, and self-compiled general information questionnaire. Results: The total EIS score of psychiatric nurses was 3.848±0.459. The highest score was for others’ emotional management (4.071±0.548) and the lowest was for emotion perception (3.684±0.483). EIS and positive coping style were statistically significant based on age, work experience, professional title, education level, and gender (P<0.05, P<0.01). Self-acceptance was statistically significant only for professional titles (F=3.258, P=0.021). Self-acceptance and emotional intelligence were positively correlated with positive coping style (r=0.361, p <0.01; r=0.492, p <0.01, respectively). The factors were also positively correlated with each other (r=0.316, P<0.01). Self-emotion management, others’ emotional management, emotion perception, self-acceptance, and education level jointly predicted positive coping styles (R2=0.305, F=60.476, P=0.000). Emotional intelligence partially mediated the relationship between self-acceptance and positive coping styles, with a mediating effect of 16.3%. Conclusion: Emotional intelligence and self-acceptance can promote positive coping styles and improve psychiatric nurses’ mental health.